Pemberdayaan UMKM melalui Pembinaan Penguatan Branding dan Digitalisasi untuk Mendukung Smart Ecotourism Kelurahan Tugurejo Kota Semarang - Milcha Fakhria; Churun A’in; Siti Rudiyanti; Adesty Aura Megarani (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Tugurejo Village is located in the Tugu District, Semarang City. The area has abundant natural resources in the fisheries sector and is supported by the surrounding mangrove ecosystem. The availability of these natural resources has encouraged the community to develop food processing through Micro, Small, and Medium Enterprises (UMKM). The challenges faced by UMKMs include a lack of understanding of business legality, underdeveloped product packaging and brand identity, and limited use of digital technology. This community service program aims to enhance the capacity of UMKM actors in Tugurejo Urban Village, Semarang City, in terms of branding and business digitalization to support the development of locally-based coastal smart ecotourism. The approach used in this community service program is Participation Action Research (PAR), where the subjects are UMKM actors. The program was implemented through a series of socialization and technical assistance activities, covering branding education, product packaging, signage, promotional banners, and the development of a shared website: putritirangtugurejo.com.  These activities were able to increase the knowledge and skills of UMKM actors in Tugurejo Village. The results indicate a significant improvement in UMKM actors’ branding awareness, digital media usage, and readiness to compete in the creative economy and sustainable tourism ecosystem. This program demonstrates that collaborative and participatory approaches can effectively drive UMKMs toward becoming more adaptive, professional, and competitive in supporting smart ecotourism.